The Efforts of Kyai in Shaping Community's Political Participation on Regent Election (Study at Potoan Daya Village, Palengaan Sub-district, Pamekasan Regency) - Zahir, Muhammad (Jurnal Administrasi Publik, 2013)
This journal discusses about political approach within public administration that reflected by the efforts of Kyai in shaping community’s political participation on Regent Election which conducted in Pamekasan Regency. Based on the conducted research, the findings showed Kyai have various efforts in shaping community’s political participation which are in religious educational sector Kyai influence the students persuasively with personal status that community regard as being charismatic leader and making the Islamic agenda as a political media. In social services sector Kyai always active in guiding the citizens to preserve tradition and assist the community in development sector such as construction of water reservoirs, mosques, etc. In political sector Kyai go directly to be member of political party, legislative candidates, and stand as a candidate for Pamekasan Regent. Besides there are some factors that affect community in giving their political rights on Regent Election which are awareness of community to make Pamekasan Regency be better and money politic which is take over as Hibah that stated by Kyai .